Use of Waste Decomposer: A Study of the Organic Farming and Enhancing the Farmers’ Income Level - Gurung, Raj Kumar (Dristikon: A Multidisciplinary Journal, 2023)
This paper proposes that farmers use waste decomposers to enhance the fertility power of soil. The use of waste decomposers enhances the soil and it increases the farmer’s income doubly. This product makes the land fertile and promotes organic farming but it is not a fertilizer, just an enhancer. Organic farming has not been broadly promoted in Nepal though most people demand organic products. Organic product means organic food which enhances the human mind. Still, the farmers are using chemical fertilizers in their farms for commercial purposes, but the productive capacity of the soil has declined. The overuse of chemical fertilizers has deteriorated not only the soil health but also the human health. Slowly and gradually, the area of barren land is increasing because of chemical aggression. The main purpose of the study is to protect human health and soil health. This waste decomposer solution decomposes the wastes into organic fertilizers shortly as well as it makes the seeds bacteria-free when washed by it before sown. Healthy seeds and organic fertilizers enhance harvesting. The price of organic products is higher than that of inorganic ones. This increases the farmer’s income level. The findings of the study show that farmers’ agricultural products have not been satisfactory with the use of conventional methods of farming. This method of farming has not enhanced the farmers’ income source. This research attempts to bridge between agriculture and literature. The study adopts the descriptive survey methods and document analysis for the description and explanation of the use of waste decomposers and their benefits.